The ark of nuh - Khan Saniyasnain (India, Goodword kidz, 2011)
Prophet Nuh (Noah) was sent by Allah to guide his people, who had turned away from the truth and worshipped idols. For many years, he warned them to stop their wrongdoing and return to the worship of Allah, but most people ignored him and made fun of him.